ANTIOXIDANT ACTIVITY AND PROBIOTIC ANTI-DIABETIC EFFECTS Lactobacillus fermentum FROM BILIH FISH (Mystacoleucus padangensis) LAKE SINGKARAK - Heppy Setya Prima (Majalah Kedokteran Andalas, 2023)
Anti-oxidant activity, anti-diabetic, an alpha-glucosidase inhibitor, Lactobacillus  fermentum isolated bilih fish (Mystacoleucus padangensis) Lake Singkarak